DAMPAK KUALITAS AUDITOR DAN KOMPLEKSITAS OPERASI PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PASCA PANDEMI - Ahmat Hoirol Anam; Ajeng Tita Nawangsari (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to examine the effect of auditor quality and company operational complexity on audit delay in manufacturing companies listed on the Indonesia Stock Exchange post-pandemic. Audit delay is defined as the time interval between the fiscal year closing date and the audit report date. The population in this study included manufacturing companies listed on the IDX for the 2020–2022 period, using a purposive sampling method. Data were analyzed using multiple linear regression. The results show that auditor quality has a significant negative effect on audit delay, while company operational complexity has a significant positive effect. These findings emphasize the importance of auditor quality and controlling operational complexity in accelerating the financial reporting process in the post-pandemic era.